Differential pulse voltammetric determination of diclofenac in pharmaceutical preparations and human serum - Bilal Yilmaz; Selcuk Kaban; Bilge Kagan Akcay; Ulvihan Ciltas (Brazilian Journal of Pharmaceutical Sciences, 2015)
This article describes a differential pulse voltammetric (DPV) method for the determination of diclofenac in pharmaceutical preparations and human serum. The proposed method was based on electro-oxidation of diclofenac at platinum electrode in 0.1 M TBAClO4/acetonitrile solution. The well-defined two oxidation peaks were observed at 0.87 and 1.27 V, respectively. Calibration curves that obtained by using current values measured for second peak were linear over the concentration range of 1.5-17.5 μg mL-1and 2-20 μg mL-1 in supporting electrolyte and serum, respectively. Precision and accuracy were also checked in all media. Intra- and inter-day precision values for diclofenac were less than 3.87, and accuracy (relative error) was better than 4.12%. The method developed in this study is accurate, precise and can be easily applied to Diclomec, Dicloflam and Voltaren tablets as pharmaceutical preparation. In addition, the proposed technique was successfully applied to spiked human serum samples. No electro-active interferences from the endogenous substances were found in human serum.